Design and development of a standalone potentio-galvanostat for the fabrication of Bi-Sr-Ca-Cu-O and Na-pTS-doped polppyrole thin-films - Manzano, Enrique M. (Animo Repository, 2008)
Among the less expensive methods of fabricating thin-films is electrochemical disposition. The key-equipment is the potentio-galvanostat which on high end-systems would be composed of a computer running an expensive control software like LabView controlling an instrument-grade current source and receiving feedback from an expensive digital oscilloscope all communicating via GBIP. This cost is still prohibitive if we were to bring the research in this-films to developing countries specially to smaller universities and colleges om the country side. This paper demonstrateds that a 3-electrode Potentio-Galvanostat for the purpose of fabricating thin-films can be constructed with inexpensive and uncalibrated DC supplies by using cheap general purpose operational amplifiers as feedback control. An optional microcontroller timer that can be attached to the system for accurate timing operations was also designed and constructed.To test the accuracy of the system, varying loads were manually simulated. The system was then tested by the actual fabrication of Bi-Sr-Ca-Cu-O and Na-pTS-Doped Polyppyrole thin-films. The thin films were then analyzed for their properties.